2020
DOI: 10.3390/ijms21082729
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Function Analysis of the Reaper Homologue IBM1 in Spodoptera frugiperda

Abstract: As an important type of programmed cell death, apoptosis plays a critical role in lepidopteran insects in response to various internal and external stresses. It is controlled by a network of genes such as those encoding the inhibitor of apoptosis proteins. However, there are few studies on apoptosis-related genes in Spodoptera frugiperda. In this study, an orthologue to the Drosophila reaper gene, named Sf-IBM1, was identified from S. frugiperda, and a full-length sequence was obtained by reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…This is further supported by the fact that both IMB and MTS are essential for hid's cell death-inducing capacity [20]. Interestingly, also, the lepidopteran S-isoform is mitochondrially localized, based on immunohistochemical detection in the armyworm moth S. frugiperda [26]. At first glance, this suggests a higher level of functional conservation between the derived S-isoforms and the ancestrally organized L-isoforms in the Lepidoptera compared to that between hid vs. grim, rpr, and skl in Drosophila.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is further supported by the fact that both IMB and MTS are essential for hid's cell death-inducing capacity [20]. Interestingly, also, the lepidopteran S-isoform is mitochondrially localized, based on immunohistochemical detection in the armyworm moth S. frugiperda [26]. At first glance, this suggests a higher level of functional conservation between the derived S-isoforms and the ancestrally organized L-isoforms in the Lepidoptera compared to that between hid vs. grim, rpr, and skl in Drosophila.…”
Section: Discussionmentioning
confidence: 85%
“…In Diptera, RHG homologs have been analyzed in the blowfly species Lucilia cuprina and L. sericata [21,22], the Caribbean fruit fly species Anastrepha suspensa (Tephritidae) [23], and, most recently, the scuttle fly Megaselia scalaris [20]. In the Lepidoptera, RHG homologs have been studied in the silkmoth Bombyx mori and the fall armyworm Spodoptera frugiperda [24][25][26]. The existence of RHG homologs outside the Lepidoptera and Diptera, however, has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by the fact that both the IMB and MTS domain are essential for Hid's cell death inducing capacity (Yoo et al 2017) . Interestingly, also the lepidopteran S-isoform is mitochondrially localized based on immunohistochemical detection in the armyworm moth S. frugiperda (Shu et al 2020) , suggesting at a higher level of functional conservation between the derived S-and ancestrally organized L-isoforms in the Lepidoptera compared to that between hid vs grim , rpr , and skl in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…The first RHG homologs identified outside dipterans via bioinformatic search in a new genome sequence was Ibm1 of B. mori (Bryant et al 2009) , which is now identified as the derived S-isoform of the B. mori RHG homolog locus. Paralleling the situation in mosquitoes, it is the ancestrally organized L-RHG isoform that has to be studied (Bryant et al 2009;Shu et al 2020) . Future analyses of both lepidopteran isoforms have the potential to inform about the subfunctionalization trajectories of newly emerging RHG homologs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation